The structure of Irish industry - Linehan, T. P. (Statistical and Social Inquiry Society of Ireland, 1962)
The development over time of Irish industry is fairly well documented, statistically speaking, in so far as production, employment etc. data are concerned for industry as a whole and for the various industrial subdivisions. The existing mechanisms of the Annual Census of Industrial Production, together with the more up-to-date (sample) inquiry carried out quarterly, are reasonably adequate to enable us to measure, as they occur, the overall developments which it is generally anticipated will follow on expansion in the membership of the Common Market. It is clear, however, that apart from external considerations these developments will be related to the intrinsic structure of Irish industry as it exists today, its size, location, etc. It may well be that the next decade will see substantial changes in the structure. To assess, in due course, the changes referred to it is necessary to have available for a recent year a detailed analysis of the industrial sector in Ireland. Indeed any scientific attempt to assess in advance the possible course of development for individual industries must take due account of size of enterprise, location etc.
Read before the Society, 18 May 1962
Keywords: Irish industry structure; Census of Industrial Production; European Common Market; 314.15